Características anatômicas e fisiológicas de cafeeiros irrigados em diferentes níveis de adubação - Gama, Tamara Cubiaki Pires da (2015)
Mineral nutrition contributes to the composition of the structural organization, causing changes in its anatomical structure that can change the tissue thickness and pigment content. The objective was to identify changes in the anatomy and physiology of coffee in different fertilizer levels (40, 70 100, 130 and 160%) in the first and second year after deployment. The first experiment consisted of coffee fertilized at different levels in the first year after implantation of the crop, being evaluated on the anatomical and physiological characteristics, as well as productivity in two seasons. The different levels of fertilization and assessment time caused differences in the internal structure, ie, the leaf anatomy and physiology of irrigated coffee. In general, the best results in the evaluated parameters were found at the level of 100% of fertilization, thus confirming the importance of mineral nutrition; and increased productivity was achieved at the level of 126% of fertilization. The second experiment was conducted with coffee fertilized at different levels in the second year after plowing of implementation, where we evaluate the characteristics of gas exchange, leaf anatomy and productivity in both rainy and dry seasons. Different levels of fertilization and assessment time caused differences in the internal structure, ie, in the leaf anatomy and physiology of irrigated coffee. The highest yield occurred at the level of 104% of fertilizer.